The impact of service quality on satisfaction and its relationship with the intention of word-of-mouth recommendation of savings and loan cooperatives: the case of Caja Popular Mexicana - Santarriaga Pineda, Maria de los Dolores; Soto Ramírez, Francisco Carlos (Cooperativismo & Desarrollo, 2023)
Savings and loan cooperatives have played a leading role in the social economy. This quantitative study with a descriptive-correlational approach analyzed the relationship between the quality of service and the satisfaction in the consumption of the members of the Caja Popular Mexicana and the impact it has with the word of mouth (WOM) recommendation. . With a sample of 308 active members, using a questionnaire as a measurement instrument. The questionnaire was designed using scales from previous studies; the analysis was done through structural equations. The results of the investigation conclude that the quality of service is associated with satisfaction and this in turn is associated with word of mouth recommendation.